The Impact of Parenting Patterns During The Pandemic on Early Children's Development - Rachmawati, Endah; Yuliantina, Irma (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
Although this can be expected, parents are more inclined to provide their kids with technology to help them learn. This study aims to ascertain how parenting affects the development of young children. Expost facto research is used in this research style together with quantitative data collection techniques. Independent samples testing is used in inferential statistics during data analysis. The results demonstrate that parenting has an impact on young children's development that is good. Where the majority of parents practice democratic parenting, or about 85.4%, it can be inferred that parenting is based on transparency and acknowledging children's accomplishments in terms of early childhood development. Collaboration between teachers and parents is necessary to support the parenting roles that parents have taken on for young children, particularly during the COVID-19 pandemic..